213 Increased Standardized Ileal Digestible Isoleucine to Lysine Ratio Improved Feed Efficiency in Pigs Fed Distillers Dried Grains with Solubles from 11 to 80 kg. (7th May 2021) - Xue, Pengcheng; Pilcher, Chad M; Li, Qingyun; Saddoris-Clemons, Kari L
Abstract: An experiment was conducted to determine the impact of dietary SID Ile to Lys ratio on the performance pigs from 11 to 80 kg of BW. A total of 1, 092 pigs (initial BW = 11.1, SEM = 0.6 kg; 14 pens/treatment; 13 pigs/pen) were used in an 80d trial with a randomized complete block design. Dietary treatments were in a 2 x 3 factorial arrangement containing 2 levels of DDGS (0 and 25%) and 3 levels of SID Ile/Lys (0.54, 0.58, and 0.62). Energy and nutrient levels of all treatments were formulated at equal levels that met or exceeded NRC (2012) requirements. The SID Ile/Lys ratio was controlled by crystalline Ile. The MIXED procedures of SAS 9.4 were employed for statistical analysis. Orthogonal contrasts were used to test for main effects of DDGS and SID Ile/Lys. In the results, formulating with 25% DDGS decreased FBW, ADG, and ADFI (P < 0.05) of growing pigs. The average FBW of treatments without and with 25% DDGS were 81.7 and 78.6 kg, respectively. The ADG of diets without and with DDGS were 0.88 vs 0.84 kg/d, respectively. The ADFI of treatments without DDGS were 1.85 kg/day, while the counterparts of treatments fed diets containing 25% DDGS were 1.79 kg/d. Feeding diets containing 25% DDGS tended to decrease Gain:Feed (0.477 vs. 0.472; P < 0.10). Increasing the level of SID Ile/Lys (from 0.54 to 0.62) linearly increased Gain:Feed in pigs fed diets containing 25% DDGS (0.467, 0.471, 0.477, respectively; P < 0.05). In summary, this study demonstrated feeding diets containing 25% DDGS decreased the performance of growing pigs by reducing ADG and ADFI. Greater SID Ile/Lys in diets may help reduce the negative impact of DDGS diets in grow-finishing pigs by improving feed efficiency.